2008
DOI: 10.1111/j.1469-8986.2008.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental stress and trapezius muscle activation under psychomotor challenge: A focus on EMG gaps during computer work

Abstract: Momentary reductions in the electrical activity of working muscles (EMG gaps) contribute to the explanation for the relationship between psychosocial stress and musculoskeletal problems in computer work. EMG activity and gaps in the left and right trapezii were monitored in 23 participants under low and high mental workload (LMW and HMW) demands during computer data entry. Increases in EMG activity and decreases in EMG-gap frequencies in both left and right trapezius muscles were greater during HMW than LMW. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 30 publications
2
72
0
Order By: Relevance
“…Even for the most common muscle studied which is the trapezius muscle, the effect of stress on muscle activity can be divided into two main groups. One group found that when a certain psychosocial stress exists, the trapezius muscle will become affected and the muscle activity will be increased significantly [8,12,18,21,[29][30][31]35]. On the other hand, another group of researchers found that the existence of a certain psychosocial stress did not have any significant effect on trapezius muscle activity [9,14,18,19,23,24,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Even for the most common muscle studied which is the trapezius muscle, the effect of stress on muscle activity can be divided into two main groups. One group found that when a certain psychosocial stress exists, the trapezius muscle will become affected and the muscle activity will be increased significantly [8,12,18,21,[29][30][31]35]. On the other hand, another group of researchers found that the existence of a certain psychosocial stress did not have any significant effect on trapezius muscle activity [9,14,18,19,23,24,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of laboratory studies lies in the better control and standardization of the task conditions to estimate the demands in terms of physical and mental workloads, which are diYcult to do in the Weld setting. In many studies that examined the eVects of mental pressure, the design tended to focus more on the proximal spinal muscles (Bansevicius et al 1997;Blangsted et al 2004;Hägg and Aström 1997;Johnston et al 2008;Lundberg et al 2002;McLean and Urquhart 2002;Schleifer et al 2008). Increase in muscle activity of the trapezius and levator scapulae have been reported when subjects performed typing with increased pace and under the additional stress of distraction (McLean and Urquhart 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have attempted to examine the eVects of mental workload or mental stressors on muscle activation during diVerent forms of computer work, which included Weld investigations (Hägg and Aström 1997;Rissén et al 2002;Vasseljen and Westgaard 1995;Wahlström et al 2003) and laboratory studies (Bansevicius et al 1997;Blangsted et al 2004;Finsen et al 2001;Hughes et al 2007;Johnston et al 2008;Krantz et al 2004;Leyman et al 2004;Lundberg et al 2002;McLean and Urquhart 2002;Nilsen et al 2007;Schleifer et al 2008;Van Galen et al 2002;Visser et al 2004). Many of these studies aimed to diVerentiate the eVects due to physical and mental workloads.…”
Section: Introductionmentioning
confidence: 97%
“…Results of some studies indicate that both types responses evoke similar responses, while other studies suggest that responses vary, depending on the kind of physical and mental tension in a given test [17]. The increased contraction of Trapesius muscle was revealed by the EMG record in the subjects performing various psychomotor tasks [40]. The test assessing muscle activity during work performed at a computer work station revealed higher activity of the upper trapezius muscle at the side opposite to the computer mouse [41].…”
Section: Fig 2 Parametersreflectingheartratevariability(hrv)atdiffementioning
confidence: 99%